PRE-EMPTIVE GOAL PROGRAMMING METHOD FOR OPTIMIZING PRODUCTION PLANNING - Hasbiyati, Ihda; Desri, Rama; Gamal, Moh Danil Hendry (PATTIMURA UNIVERSITY, 2023)
In this paper the mathematical modelling of production planning is put forward using the pre-emptive goal programming method for priority based decision making. The objective of this problem is to design production planning satisfying the speciﬁed constraints while minimizing deviations from each goal to be achieved. The goals consist of ﬁve types of best seller bread, production proﬁts, production costs, production quantities, and availability of bread raw materials. LINGO 11.0 package is implemented for computational purposes. Computational results show that the pre-emptive goal programming is an efficient method for optimizing production planning of multiple goals based on the order of priority.